Mechanistic insights into the HPF1/PARP1 complex - Zobel, FFH (2021)
ADP-ribosylation is a vital post-translational modification associated with a large range of processes including DNA damage repair, transcription, replication, mitosis, inflammation and cell death. ADP-ribosylation arises through the covalent attachment of ADP-ribose from NAD+ onto target proteins. The modification strongly varies in size, ranging from a single ADP-ribose unit (MARylation) to large, branched chains (PARylation). In humans, one major family of ADP-ribosyltransferases constituting 17 members are poly-ADP-ribose polymerases (PARPs). Their most prominent member, the nuclear protein PARP1, alone is responsible for the overwhelming majority of ADP-ribosylation in cells. While PARP1 was originally described to modify target substrates on glutamate and aspartate sites, it has become apparent in recent years that the presence of another protein, histone PARylation factor 1 (HPF1), switches its preference to serine target sites. Following this discovery, serine ADP-ribosylation was shown to be the main type of ADP-ribosylation in response to DNA damage. However, how HPF1 engages with PARP1 and is able to change the nature of its catalytic activity has remained unclear. This thesis explores the interaction between HPF1 and PARP1 in human cells, the molecular basis of HPF1/PARP1-catalyzed serine ADP-ribosylation and the consequences of aberrations in both proteins. Crucially, colleagues and I describe the interaction sites on both proteins and show that HPF1 in cells is required for the catalytic completion of PARP1 through a glutamate "finger". Furthermore, we identify the main sites of PARP1 serine auto-modification and illustrate their significance for PARP inhibitor-resistant PARP1 auto-modification and the release of PARP1 from sites of DNA damage. Finally, we explore in human cells the phenotypic consequences of losing the main PARP1 serine auto-modification sites, the HPF1 catalytic glutamate finger or HPF1-PARP1 interaction. Altogether, these results draw a comprehensive picture of HPF1-PARP1 mechanistic functions and the wider implications of its disruption.